Humanitarian supply chain performance management: a systematic literature review. Issue 5 (2nd September 2014) - Abidi, Hella; de Leeuw, Sander; Klumpp, Matthias
Abstract : Purpose: – This paper aims to identify the state of the art of performance measurement and management in humanitarian supply chains; to categorize performance measurement indicators in the five supply chain phases of Gunasekaran and Kobu (2007) and evaluate them based on the evaluation criteria of Caplice and Sheffi (1995); and to define gaps and challenges in this field and give insights for future research in this domain. Design/methodology/approach: – A literature review has been conducted using a structured method based on Denyer and Tranfield (2009) and Rousseau et al. (2008). The state of the art on humanitarian supply chain performance management with a focus on measurement frameworks and indicators and their applications in practice is classified in three categories. The first category is the definition and measurement of success in humanitarian supply chains. The second category is managing performance, which focuses on describing and analyzing the actual practice of managing performance. The third category shows the challenges in performance management that humanitarian supply chain actors deal with. Findings: – Findings reveal that performance measurement and management in humanitarian supply chains is still an open area of research, especially compared to the commercial supply chain sector. Furthermore, the research indicates that performance measurement and management in humanitarian supply chains has to be developed in support of the supply chain strategy. Based on the findings of the literature review on performance measurement and management in the commercial and humanitarian field, a first classification of 94 performance measurement indicators in humanitarian supply chains is presented. Furthermore, the paper shows key problems why performance measurement and management systems have not been widely developed and systematically implemented in humanitarian supply chains and are not part of the supply chain strategy. The authors propose performance measurement guidelines that include input and output criteria. They develop a research agenda that focuses on four research questions for designing, deploying and disseminating performance measurement and management in humanitarian supply chains. Practical implications: – The result helps the humanitarian supply chain community to conduct further research in this area and to develop performance measurement frameworks and indicators that suit humanitarian supply chains. Originality/value: – It is the first systematic approach to categorize research output regarding performance measurement and management in humanitarian supply chains. The paper shows the state of the art in performance measurement and management in humanitarian supply chains and develops a research agenda.